Handbook of transport systems and traffic control - Hensher, David A., 1947-; Button, Kenneth, 1948- (Emerald, 2001)
This book discusses transport systems and the implementation of related public policy - a relevant topic with contemporary traffic congestion, environmental intrusion, transport safety, and budget issues. It is a resource for both experienced researchers and those new to the field.
Includes indexes.
Keywords: Transportation -- General.; Transportation -- Public Transportation.; Transport industries.; Economic systems & structures.; Transportation engineering -- Handbooks, manuals, etc.; Traffic engineering -- Handbooks, manuals, etc.; elektronické knihy; electronic books